A realidade aumentada como método pedagógico no ensino de química - SOARES, Ericson Castanheira (2024)
The use of Augmented Reality (AR) in education is becoming increasingly widespread. It can cooperate with teaching activities and arouse students' interest, stimulating the learning process. In identifying the problem, we asked: what are the difficulties encountered by students in high school and technical-vocational education in assimilating chemistry content? To answer this question, the research will use AR as a pedagogical tool with the purpose of demonstrating its importance in teaching chemistry. The work is divided into three parts: the first will address the bibliographic review in the light of theorists; the second will present the methodology to be applied; and finally the conclusive results of the data collected. Given this problem, the research proposes to apply ICTs in the teaching of Chemistry, with the use of two freely accessible AR applications (quimicAR and modelAR) available in the Android app stores. In May 2024, in Brazil, approximately 81.38% used this operating system as a pedagogical methodology in the teaching-learning process. Augmented Reality technology applied to Chemistry teaching has shown great promise due to the results of class progress: 1st year of high school of EEGD of 37.50%, 2nd year of high school of EEGD of 20.00%, technical course in food, first year in the integrated form of IFAP of 6.25%, technical course in food, third year in the integrated form of IFAP of 12.50%, technical course in chemistry, first year in the integrated form of IFAP of 12.50% and technical course in chemistry, third year in the integrated form of IFAP of 5.00%. It is believed that students who have difficulties with the Chemistry subject, notably due to the abstraction of some concepts and models, will be able to overcome obstacles and better assimilate/understand the chemical knowledge studied. Keywords: digital technologies; augmented reality; study of chemistry.